One piece. Collection no. 18 [videorecording (DVD)] (Funimation, 2017)
Luffy and Hancock arrive at the underwater prison of Impel Down, where the Snake Princess uses every ounce of her beguiling charm to smuggle him past the guards. Once inside, unexpected alliances help Luffy survive the increasingly dangerous levels of the prison. At the depths of it all lies the poisonous Warden Magellan whose toxins put the rubber-man's life at stake.